FRI0318 Quality of life in patients with behcet's disease. (15th June 2017) - Santos-Faria, D; Silva, JL; Cerqueira, M; Rodrigues, JR; Sousa-Neves, J; Teixeira, F; Peixoto, D; Tavares-Costa, J; Afonso, C; Alcino, S
Abstract : Background: Behcet's disease (BD) is a chronic and multisystemic inflammatory disorder affecting the skin, mucosa, joints, eyes, arteries, veins and the nervous and gastrointestinal systems. The symptoms may be separated by long or short intervals, occur simultaneously or in sequence, and exhibit a pattern of exacerbation and remission. The disease itself or the impact of the symptoms affect patients physically, mentally and socially with a negative effect in the quality of life (QoL). Objectives: To determine the health status and quality of life in patients with BD followed in a rheumatology unit and to identify associated demographic and disease-related parameters influencing them. Methods: Cross-sectional study of 44 BD patients and 39 healthy controls matched for age and sex. All subjects completed the Health Assessment Questionnaire (HAQ) to assess impairment in daily activities due to illness, Short Form-36 (SF-36) and EuroQol Visual Analogic Scale (EQ-VAS) to assess health related quality of life (HRQL). The disease characteristics, including disease duration and clinical involvements were collected. The Birmingham Vasculitis Activity Score (BVAS) was applied for the evaluation of current disease activity among BD patients. P value <0.05 was defined as statistically significant. Results: Among 44 patients, 35 (79.5%) were female, with a mean age of 40.07 years and mean disease duration of 5.93 years. BD patients had significantly higher HAQ score (p=0.009) and lower levels of SF-36 (p<0.001) than the healthy controls. The predominant contributors to this low SF-36 were general health, vitality and role-emotional domains. In comparison with healthy controls, patients with inactive disease (BVAS=0) also had a higher HAQ, but without significant differences (p=0.53). The total SF-36 score also showed lower levels in patients with inactive disease (p=0.04), but when compared the different components, only half of them maintained significant differences, namely role-physical (p=0.03), general health (p<0.001), vitality (p<0, 001) and social functioning (p=0.05). The controls showed a higher EQ-VAS, with a mean of 88.44 comparing to 68.36 in all BD patients (p<0.001) and 74.12 in the subgroup with inactive disease (p=0.003). SF-36 score was negatively correlated with HAQ (r=-, 553, p<0.001) and positively correlated with EQ-VAS (r=.388, p<0.001). Longer disease duration correlated with lower levels of only some SF-36 domains, namely physical functioning (r=-.436, p=0.003), role-physical (r=-.533, p<0.001) and role-emotional (r=-.465, p=0.001). There was no correlation between disease activity and disease duration (p=0.678) or different scores evaluating QoL (p=0.876). The gender was not associated with statistical differences when compared clinical involvements, disease duration, current disease activity, HAQ, EQ-VAS or SF-36 scores. The heterogeneous nature of the disease expression did not allow the study of the association with the levels of health status and QoL. Conclusions: Our findings showed lower levels of QoL and global health status in BD compared to healthy controls, mainly in active disease, accordingly with previous studies. The disease itself could be a determinant of disability. References: Melikoglu M, Melikoglu MA. What affects the quality of life in patients with Behcet's disease? Acta Reumatol Port. 2014;39(1):46–53. Disclosure of Interest: None declared